Imposed Form in the Early Acheulean? Evidence from Gona, Afar, Ethiopia - Stout, Dietrich; Liu, Cheng; Muller, Antoine; Rogers, Michael; Semaw, Sileshi (Journal of Archaeological Method and Theory, 2025)
Keywords: Acheulean; Ancient history; Anthropology; Archaeology; Early Stone Age; Ethnology; Geography; Handaxe; History; Large cutting tool; Lithic technology; Pick; Pleistocene; Shaping; Sociology; dept.ant

Co-occurrence of Acheulian and Oldowan artifacts with Homo erectus cranial fossils from Gona, Afar, Ethiopia. - Semaw, Sileshi; Rogers, Michael J; Simpson, Scott W; Levin, Naomi E; Quade, Jay; Dunbar, Nelia; McIntosh, William C; Caceres, Isabel; Stinchcomb, Gary E; Holloway, Ralph L; Brown, Francis H; Butler, Robert F; et al. (Science advances, 2020)
Although stone tools generally co-occur with early members of the genus Homo, they are rarely found in direct association with hominins. We report that both Acheulian and Oldowan artifacts and Homo erectus crania were found in close association at 1.26 million years (Ma) ago at Busidima North (BSN12), and ca. 1.6 to 1.5 Ma ago at Dana Aoule North (DAN5) archaeological sites at Gona, Afar, Ethiopia. The BSN12 partial cranium is robust and large, while the DAN5 cranium is smaller and more gracile, suggesting that H. erectus was probably a sexually dimorphic species. The evidence from Gona shows behavioral diversity and flexibility with a lengthy and concurrent use of both stone technologies by H. erectus, confounding a simple "single species/single technology" view of early Homo. Copyright © 2020 The Authors, some rights reserved; exclusive licensee American Association for the Advancement of Science. No claim to original U.S. Government Works. Distributed under a Creative Commons Attribution NonCommercial License 4.0 (CC BY-NC).
40 citations (Crossref) [2023-10-31] Place: United States Semaw, Sileshi. Centro Nacional de Investigacion sobre la Evolucion Humana (CENIEH), Sierra de Atapuerca 3, 09002 Burgos, Spain. Semaw, Sileshi. Stone Age Institute and CRAFT Research Center, 1392 W. Dittemore Rd., Gosport, IN 47408, USA. Rogers, Michael J. Department of Anthropology, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, USA. Simpson, Scott W. Department of Anatomy, Case Western Reserve University School of Medicine, Cleveland, OH 44106, USA. Simpson, Scott W. Laboratory of Physical Anthropology, Cleveland Museum of Natural History, Cleveland, OH 44106, USA. Levin, Naomi E. Department of Earth and Environmental Sciences, University of Michigan, 1100 North University Avenue, Ann Arbor, MI 48109, USA. Quade, Jay. Department of Geosciences/Desert Laboratory, University of Arizona, Tucson, AZ 85721, USA. Dunbar, Nelia. New Mexico Bureau of Geology and Mineral Resources, Earth and Environmental Science Department, New Mexico Tech, 801 Leroy Place, Socorro, NM 87801-4796, USA. McIntosh, William C. New Mexico Bureau of Geology and Mineral Resources, Earth and Environmental Science Department, New Mexico Tech, 801 Leroy Place, Socorro, NM 87801-4796, USA. Caceres, Isabel. Universitat Rovira i Virgili (URV), Avinguda de Catalunya 35, 43002 Tarragona, Spain. Caceres, Isabel. IPHES, Institut Catala de Paleoecologia Humana i Evolucio Social, Zona Educacional 4-Campus Sescelades URV (Edifici W3), 43007 Tarragona, Spain. Stinchcomb, Gary E. Watershed Studies Institute and Department of Earth and Environmental Sciences, Murray State University, Murray, KY 42071, USA. Holloway, Ralph L. Department of Anthropology, Columbia University, 1200 Amsterdam Ave., New York, NY 10027, USA. Brown, Francis H. The University of Utah, 201 South Presidents Circle Room 201, Salt Lake City, UT 84112, USA. Butler, Robert F. Department of Physics, University of Portland, Portland, OR 97203, USA. Stout, Dietrich. Department of Anthropology, Emory University, 1557 Dickey Drive, Atlanta, GA 30322, USA. Everett, Melanie. Chevron Energy Technology Company, 1500 Louisiana St., Houston, TX 77002, USA.
Keywords: *Biological Evolution; *Fossils; *Hominidae; *Skull/ah [Anatomy & Histology]; Animals; Archaeological site; Behavioral diversity; Biodiversity; Biological Evolution; Co-occurrence; Ethiopia; Fossils; Hominidae; Hominidae/ah [Anatomy & Histology]; Hominidae/cl [Classification]; Hominins; Homo erectus; Humans; Paleontology; Single species; Skull; anatomy and histology; animal; classification; dept.ant; evolution; fossil; hominid; human; paleontology; peer-reviewed; skull